Prevalence and Determinants of Depression among Diabetic Patients,Babel Province, Iraq, 2013-2014 - Al Maliki, Ashraf; Lami, Faris; Al Aboudi, Sha’alan (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Diabetes Mellitus is a complex chronic disease, requiring continuous medical care with multi factorial risk reduction strategies beyond glycemic control. Approximately 30% of patients with types 1 and type 2 diabetes had depression. In addition to the high risk of complications and poor glycemic control, individuals with both diabetes and depression have a 2-3 times greater risk of early mortality than do nondepressed people with diabetes. Early detection of this comorbidity is worthy, especially with simple and relatively valid scales.Objectives: To identify the prevalence and potential risk factors of depression among diabetic patients in Babel province, 2013-2014Patient and Method: A cross-sectional study conducted in Marjan Hospital, diabetes Center, Babel, October, 1st, 2013 to April, 1st, 2014. The study included all patients with Type1 & 2 diabetes excluding pregnant women and those with advanced complications. Data on socio-demographic variables, diabetes characteristics and presence of comorbid diseases and complications was compiled. Self Reporting Questioner (SRQ-20) to identify mental illnesses; DSM-IV criteria for depression and Hamilton-17 Scale, for assessment of severity of depression were used.Results: A total of 466 patients were approached; 91.2% responded. About 90% were of type 2 DM; 37% had depression; 78% had mild and only 4% had severe and very severe depression. Presence of depression was significantly associated with age (P=0.000), marital status (0.036), type of treatment (P=0.001), presence of Ischemic Heart Diseases (P=0.000); retinopathy (0.012), and neuropathy (0.000).Conclusions: More than one third of diabetic patients had depression. Age, type of treatment, and presence of other comorbid conditions or complications were significant risk factors.